The RADEC learning model assisted by an e-learning application in fostering the high-order thinking skills of aspiring primary school teachers - Nursiwi Nugraheni; Trimurtini Trimurtini; Elok Fariha Sari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This paper investigates the performance of the RADEC learning model(TRLM) assisted by e-learning to foster higher-order thinking skills (HOTS) in aspiring primary school teachers. No one has researched HOTS in the implementation of TRLM, which is held online in mathematics materials. A quasi-experimental design was employed in this research. Aspiring primary school teachers who are studying at Semarang State University were the subject of this paper. The aspiring primary school teachers are currently in their second semester of study. There were two classes through simple random sampling: one performed TRLM assisted by e-learning, and one control class. HOTS was measured using essay questions with HOTS indicators, specifically analysing, evaluating, and creating. The question was valid and reliable. The study results showed that the average post-test score of the experimental class was higher than that of the control class. There is an increase from pretest to posttest in both the control and experimental classes. However, when checked, the N-Gain score percentage of the experimental class showed that the increasing HOTS is quite effective. At the same time, the control class was ineffective. TRLM-assisted e-learning increases the HOTS of aspiring primary school teachers and is more effective than the control class.